The Difference In Qirâ'ât Al-Qur'an Is Seen From The Rules Of Arabic According To Abduh Al-Rajihi In The Book Al-Lahjât Al-'Arabiyyah Fi Al-Qirâ'ât Al-Qur'âniyyah - Ekawati, Ekawati; Ivada, Putra Dian Kharisma (Enrichment: Journal of Multidisciplinary Research and Development, 2023)
The aim of this research is to analyze and describe analitically the difference in " qirâ’ât al-Qur’an" from the point of view of Arabic language structure. The writer applies qualitative method. In discussing the problems of this research, she applies library research by using comprehensive and comparative approaches. The result shows that the difference in "qirâ’ât al-Qur’an" analyzed by " qawâ`id" aspects in Arabic language can be classified into "mustawâ sharfî" (morphological aspects), and " mustawâ nahw" (syntactic aspects).